CLINICAL FACTORS ASSOCIATED WITH PAIN INTENSITY AND ADJUVANT ANALGESIC USE IN OSTEOARTHRITIS PATIENTS - Nuh Muhammad; Darmawan Endang; Surono Sugiyarto (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2026)
Osteoarthritis (OA) is a degenerative joint disease that commonly causes chronic pain and functional limitations. In routine practice, adjuvant analgesics are frequently used as part of multimodal pain management; however, clinical factors associated with pain intensity and adjuvant analgesic use are not well characterized. This retrospective observational study aimed to identify clinical factors associated with final pain intensity and their relationship with adjuvant analgesic use in patients with OA. Medical records of OA patients treated at Sultan Agung Islamic Hospital, Indonesia, between 2020 and 2025 were reviewed. Data included patient characteristics, OA severity based on the Kellgren–Lawrence (KL) grading system, pain intensity assessed using the Visual Analog Scale (VAS), and types of adjuvant analgesics prescribed, Multivariate logistic regression analysis showed that severe OA (KL grade ≥3) was the strongest factor associated with higher final pain intensity (OR = 3.56; 95% CI: 2.9–4.3). Knee OA (OR = 1.70; 95% CI: 1.1–2.4) and hyperlipidemia (OR = 2.33; 95% CI: 1.3–4.1) were also independently associated with higher final pain intensity. The use of adjuvant analgesics, particularly joint supplements and neuropathic pain agents, was associated with higher final pain intensity, reflecting greater disease severity and clinical complexity rather than direct analgesic effectiveness. Muscle relaxants were not significantly associated with pain intensity. In conclusion, final pain intensity in OA is primarily associated with disease severity and clinical complexity, and causal relationships cannot be established due to the observational design.